INFORMATION OVERLOAD AND INDIVIDUAL INVESTORS’ PERCEPTIONS OF INVESTMENT RISK: EVIDENCE FROM SAUDI ARABIA - Aref M. Eissa; Ahmed Diab; Meshal Obaid Almutairi; Amr N. Abdelrhman (International Journal of Business and Society, 2024)
This study explores investors’ perceptions of investment risk under information overload. We use a survey of 133 individual investors in the Kingdom of Saudi Arabia (KSA), and to test our hypotheses, we employ descriptive statistics and sample t-test. We found that information overload in lengthy annual reports decreases investors’ confidence in the financial statements and reduces their ability to understand the firm’s business and financial performance. Investors confirmed that information overload reduces their ability to access relevant information for making investment decisions and predict future performance, and increases uncertainty about the firms’ future performance. Consequently, information overload increases investors’ perceptions of firms’ investment risk, reduces their confidence to invest in firms with long and difficult-to-read annual reports, and increases their perceptions of the likelihood that these reports are being exploited by managers to hide poor performance or earnings manipulation, and consequently, they prefer not to invest in these firms. In addition, the results indicated that disclosure complexity along with information overload exacerbates investors’ negative perceptions about the firm’s investment risk and its performance. Our results provide insights for investors in emerging markets such as the Saudi market to understand the negative implications of information overload, which can enlighten their investment decisions.